Serum Metabonomics Reveals Key Metabolites in Different Types of Childhood Short Stature - Chen, Guoyou; Wang, Jinming; Jing, Yisi; Li, Chunxiang; Zhang, Wenyue; Yang, Shuang; Song, Ye; Wang, Xin; Liu, Jincheng; Yu, Dejun; Xu, Zhichun (Frontiers in Pharmacology, 2022)
Nowadays, short stature (SS) in childhood is a common condition encountered by pediatricians and is an increase in not just a few families. Various studies related to the variations in key metabolites and their biological mechanisms that lead to SS have increased our understanding of the pathophysiology of the disease. However, little is known about the role of metabolites variation in different types of childhood SS that influence these biological processes and whether the understanding of the key metabolites from different types of childhood SS would predict the disease progression better. We performed a systematic investigation using the metabonomics method and studied the correlation among the three groups, i.e., the control, idiopathic short stature (ISS), and short stature due to growth hormone deficiency (GHD). We observed that three pathways (purine metabolism, sphingolipid signaling pathway, and sphingolipid metabolism) were significantly enriched in childhood SS. Moreover, we reported that two short peptides (Thr Val Leu Thr Ser and Trp Ile Lys) might play a significant role in childhood SS. Various metabolites in different pathways including 9,10-DiHOME, 12-HETE, and 12(13)-EpOME, arachidonic acid methyl ester, glycerophospho-N-arachidonoyl ethanolamine, curvulinic acid (2-Acetyl-3,5-dihydroxyphenyl acetic acid), nonanoic acid, and N'-(2,4-Dimethylphenyl)-N-methylformamidine in human serum were investigated between 60 children diagnosed with SS and 30 healthy children. More investigations in this area may provide insights and enhance the personalized treatment approaches in clinical practice for SS through elucidating pathophysiology mechanisms of experimental verification.